Chronic Suppurative Otitis Media Type Benign Left Auricle: A Case Report - Rilla Dilvianika; Puji Sulastri; Anggri Murtia (International Journal Labs, 2025)
Chronic suppurative otitis media (OMSK) is an infection of the middle ear that can cause significant hearing loss and complications. In this case report, a 65-year-old male patient complained of discharge from the left ear for two weeks, accompanied by pain and hearing loss. Physical examination showed perforation of the tympanic membrane and mucopurulene secretion. The occupational diagnosis is a benign type of OMSK auricula sinistra. Management includes medical therapy and patient education about CSOs. The patient's prognosis shows a good expectation of recovery with proper treatment.